Self-adaptive algorithms with inertial effects for solving the split problem of the demicontractive operators - Raweerote Suparatulatorn (2020)
© 2019, The Royal Academy of Sciences, Madrid. The purpose of this paper is to introduce two new versions of self-adaptive algorithms by using inertial effects for solving the split common fixed point problem of demicontractive operators in Hilbert spaces and prove its weak and strong convergences under some weakened assumptions. Furthermore, we provide numerical experiments to illustrate the convergence behavior and efficiency of our proposed algorithms.